Effects of participation in contact sports on neurocognitive scores and dual-task walking in retired athletes - Ha, S. (Korean Journal of Sport Biomechanics, 2020)
Objective: The aim of this study was to investigate the effect of participation in contact sports on neurocognitive scores, dual-task walking velocity, and cognitive costs in retired athletes. Method: Forty-four retired athletes (mean age = 26.4±5.5 yrs) and thirty-eight controls (mean age = 26.1±4.9 yrs) participated in this study. Neurocognitive score was collected using computerized neurocognitive testing using RehaCom. Gait velocity was collected one single task, four dual-tasks, and two multi-tasks using Optogait. Mann-Whitney U test was performed to compared differences in cognitive scores among groups. A mixed-design two-way ANOVA and Bonferroni posthoc test were used to assess the effect of group and walking tasks for each condition. Results: The auditory divided attention of neurocognitive score of retired athletes was higher than the control group (p < 0.05). No statistical differences were observed in the other neurocognitive scores between groups. The changes in walking velocity and cognitive costs according to the dual-task walking tests differed between the two groups (p < 0.05). Conclusion: Although participation in contact sports did not affect the neurocognitive results of retired athletes, it could be confirmed that the reduction in walking velocity and an increase in cognitive costs during dual-task walking. Rather than observing only neurocognitive scores as a single evaluation item for cognitive evaluation of retired athletes in relation to daily life, the application of the dual-task gait test may provide useful information.